Lucíola: a ambigüidade na construção da personagem - Arruda, Luiza Valentina Pereira de (2009)
This paper shows the ambiguity present in the construction of a character named Lúcia in the book Lucíola, wrote by José de Alencar. The first chapter traces a short historical path showing several theorics perspectives about character. The chapter II analizes the differences between a public woman and a cast woman showed in some books of the Brazilian Literature. These differences presents in these romances: Senhora, Inocência, Helena and Lucíola, were studied, determining this way the profile of the woman present at the society of XIX century. The sources used in this work were books of Literature, History and Sociology areas. This work analyses and specifies, at the chapter III, the ambiguities of Lúcia, a courtesan who falling in love, perform some changes in order to get the love related to the soul. The romance Lucíola presents a theme with strong emocional appeal and has in Lúcia a representation of a romantic ideal. The psycological complexity of the character, assures this study witch was porposed because this romance brings one more of the great woman profile of José de Alencar